2003
DOI: 10.1046/j.0309-2402.2003.02845.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse‐managed clinics: issues in evaluation

Abstract: The main argument proposed here is that a combination of qualitative and quantitative data sources is likely to give the greatest understanding of NMCs utilization. Evaluation of NMCs is vital to the continuation of this type of health service. However, evaluation must be appropriate to the service being studied. Fourth generation evaluation used to elicit client's perceptions of the clinic along with quantitative data is offered as an appropriate means of achieving this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…2000). Whether these nurses carry a specific work title that reflects their advanced practice position or their title is simply that of a qualified nurse is dependent on the setting in which they work (Clendon 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2000). Whether these nurses carry a specific work title that reflects their advanced practice position or their title is simply that of a qualified nurse is dependent on the setting in which they work (Clendon 2003).…”
Section: Introductionmentioning
confidence: 99%
“…2002). Many of the reported clinics were run by nurse practitioners (Clendon 2003), clinical nurse specialists (Mills et al. 2002) or nurses trained in the specialty areas concerned (Connor et al.…”
Section: Introductionmentioning
confidence: 99%
“…the processes of care) should be opened [13]. Process evaluations are therefore warranted and promoted [14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of patient satisfaction with a nurse led joint replacement review clinic was examined in this study, and is important as seeking consumer opinion can influence service planning and delivery (Bond and Thomas, 1992). Satisfaction with care is a perception which presents a challenge (Fitzpatrick, 1991;Bond and Thomas, 1992) and over recent years there has been an increase in the number of studies, signalling its importance in the field of health care research (Dolinsky and Caputo, 1990;Bond and Thomas, 1992;Hill et al, 1994;Hill, 1997;Garvican et al, 1998;Clendon, 2003;Miles et al, 2002;Moore et al, 2002). Ventura et alÕs (1982) research has indicated that patients will tend to indicate a high level of satisfaction even when this is clearly not the case.…”
mentioning
confidence: 99%